Cuba and revolutionary Latin America : an oral history - Kruijt, Dirk (Zed Books, 2017)
Providing the definitive oral history of the Cuban revolution, tells the powerful story of Cuba's struggle for liberation from the Batista dictatorship, its transition to socialism, and its evolving relationship with the rest of Latin American and the Caribbean. Drawing on a vast array of original testimonies, including interviews with more than seventy Cuban officials and former combatants, Dirk Kruijt examines the pivotal role of veterans and the post-revolution fidelista generation in shaping Cuba. He also reveals the untold story of the Departamento América, a clandestine and largely undocumented organization that was instrumental in exercising Cuban influence abroad. --Publisher's description.